Lignans from the leaves of Mallotus paxii - HOU Ping; REN Chenyang; HUANG Yan; PAN Liwei; PENG Liuting; GAN Chunqiu; LI Jun (Guangxi Zhiwu, 2024)
Mallotus paxii is a Euphorbiaceae plant belonging to the genus Mallotus Lour. This genus mainly distributes in tropical and subtropical Asia, and there are about 140 species in the world. There are 36 species in China, including 11 varieties, which mainly grow in Guangxi, Guangdong and Hainan. To study the compounds of Mallotus paxii, twelve lignans were isolated from the leaves of M. paxii by means of various column chromatographic techniques, including silica gel, ODS, Sephadex LH-20 and preparative RP-HPLC methods. The structures of the isolated lignans were determined on the basis of analyses of spectroscopic methods (1H- and 13C-NMR spectroscopy), high-resolution electrospray ionization mass spectrometry (HR-ESI-MS), and comparison of their spectroscopic data with previously reported data. The lignans were identified as 7″,8″-threo-buddlenol D (1), buddlenol D (2), 7″,8″-threo-buddlenol C (3), buddlenol C (4), (+)-syringaresinol (5), epipinoresinol (6), pinoresinol (7), 1-acetoxyl-2e,6e-dipiperonyl-3,7-dioxabicyclo-［3,3,0］-octane (8), ciwujiatone (9), lariciresinol-4′-O-β-D-glucopyranoside (10), rel-(2α,3β)-7-O-methylcedrusin (11), and dihydrodehydrodiconiferyl-alcohol 4′-O-β-D-glucoside (12). All compounds were isolated from M. paxii for the first time. Some lignans have good pharmacological activities such as antibacterial, anti-inflammatory, anti-tumor and anti-virus. The results of this study show that the leaves of M. paxii are rich in lignans with good activity, indicating that its good medicinal value may be related to these lignans.